Kinetics of oxidative degradation of Rhodamine-B by N-bromosuccinimide in aqueous alkaline medium - Abdel-Hady, Alaa Eldin Mokhtar (European Journal of Chemistry, 2013)
The kinetics of oxidative degradation of Rhodamine-B (RhB) by N-bromosuccinimide (NBS) in aqueous alkaline and H2O-MeOH solvent mixtures were studied spectrophotometrically over the 20-40 °C range, 0.1-0.4 mol/dm3 ionic strength, 11.3-12.1 pH range and 0-30 wt% MeOH-H2O solvent mixtures for a range of NBS and Rhodamine-B concentrations. The rate of reaction showed first order dependence on both [NBS], [RhB] and inverse first order dependent upon [OH-]. The rate decreased with decreasing the dielectric constant of the medium and was independent on the ionic strength over the range studied. An inner-sphere mechanism in which the protonated Rodamine-B, (RhBH+) was considered as the main reactive species is proposed.